Coupling of Action-Perception Brain Networks during Musical Pulse Processing: Evidence from Region-of-Interest-Based Independent Component Analysis - Burunat, Iballa; Tsatsishvili, Valeri; Brattico, Elvira; Toiviainen, Petri (Frontiers in Human Neuroscience, 2017)
Our sense of rhythm relies on orchestrated activity of several cerebral and cerebellar structures. Although functional connectivity studies have advanced our understanding of rhythm perception, this phenomenon has not been sufficiently studied as a function of musical training and beyond the General Linear Model (GLM) approach. Here we studied pulse clarity processing during naturalistic music listening using a data driven approach (independent component analysis; ICA). Participants’ (18 musicians and 18 controls) functional magnetic resonance imaging (fMRI) responses were acquired while listening to music. A targeted region of interest (ROI) related to pulse clarity processing was defined, comprising auditory, somatomotor, basal ganglia, and cerebellar areas. The ICA decomposition was performed under different model orders, i.e., under a varying number of assumed independent sources, to avoid relying on prior model order assumptions. The components best predicted by a measure of the pulse clarity of the music, extracted computationally from the musical stimulus, were identified. Their corresponding spatial maps uncovered a network of auditory (perception) and motor (action) areas in an excitatory inhibitory relationship at lower model orders, while mainly constrained to the auditory areas at higher model orders. Results revealed (a) a strengthened functional integration of action perception networks associated with pulse clarity perception hidden from GLM analyses, and (b) group differences between musicians and nonmusicians in pulse clarity processing, suggesting lifelong musical training as an important factor that may influence beat processing.